PERAN ORANG TUA DALAM PENGUATAN PENDIDIKAN AGAMA ISLAM DI LINGKUNGAN KELUARGA DI DESA PUJON KIDUL KECAMATAN PUJON KABUPATEN MALANG - Fifi Amilatus Solihah; Nur Hasan; Mutiara Sari Dewi (VICRATINA, 2020)
This study aims to 1) describe the efforts done by parents in strengthening Islamic religious education in the family environment, and 2) factors that inhibit parents in strengthening Islamic religious education in the family environment. The approach used in research is a qualitative approach to the type of phenomenological research. Data collection is done by the method of observation, interview methods, and documentation methods. Data analysis using technical data reduction, data presentation, and drawing conclusions. Data validity testing is done by comparing the sources, theories, and research techniques. This triangulation can also be done by comparing observations, interview results, and circumstances and perspectives with various opinions of others.The results of this study are 1) the efforts of parents in the Pujon Kidul village community who seek religious education in Ilsam by putting in mind the attitude and values of early childhood, controlling children's religious activities, playing an active role in children's religious activities both in the family circle and in the environment community in the sense of being an example for children, putting children in a good educational environment, and praying for them. 2) Factors that can hinder parents in strengthening Islamic religious education are environmental factors, the association of children, parenting patterns that are not good, and excessive use of samrt phone and the absence of discretion from parents on the use of smart phones.